3.6k views
0 votes
What are the solutions of the equation (x + 2)2 + 12(x + 2) – 14 = 0? Use u substitution and the quadratic formula to solve.

a. x= -8+5 square root 2b) x=-6+5 square root 2c) x= -4+5 square root 2d) x= -2+5 square root 2?

User Roman Vogt
by
6.0k points

2 Answers

4 votes
Let u = x+2. That makes our equation, in terms of u:
u^2+12u-14=0. Fitting this into the quadratic formula looks like this:
u= (-12+/- √(12^2-4(1)(-14)) )/(2). Simplifying a bit gives us
u= (-12+/- √(200) )/(2). Simplifying that in terms of the radical gives us
u= (-12+/-10 √(2) )/(2). Reducing that numerator by the 2 in the denominator gives us
u=-6+5 √(2),-6-5 √(2). If u = x + 2, then we make that substitution now to solve for x:
x+2=-6+5 √(2) and
x=-10+5 √(2);
x+2=-6-5 √(2) and
x=-10-5 √(2)
User Kumuluzz
by
5.4k points
5 votes

Answer:


\text{The solutions are}x=-8+5\sqrt2,-8-5\sqrt2

Explanation:

Given the equation


(x+2)^2+12(x+2)-14=0

we have to find the solution of above equation by using quadratic formula.


(x+2)^2+12(x+2)-14=0

Substituting x+2=u, we get

Equation:
u^2+12u-14=0


\text{Comparing above with standard equation }ax^2+bx+c=0\text{, we get}

a=1, b=12, c=-14

By quadratic formula


a=(-b\pm √(b^2-4ac))/(2a)


a=(-12\pm √((12)^2-4(1)(-14)))/(2(1))


a=(-12\pm √(200))/(2)


a=(-12\pm 10√(2))/(2)


a=-6+5√(2),-6-5√(2)


\text{The solutions for u are }-6+5√(2),-6-5√(2)


x+2=-6+5√(2) and
x+2=-6-5\sqrt2


x=-8+5\sqrt2,-8-5\sqrt2

Option A is correct

User Soroush Hakami
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.